2005
DOI: 10.1111/j.1600-079x.2005.00248.x
|View full text |Cite
|
Sign up to set email alerts
|

A proposed mechanism to explain the stimulatory effect of melatonin on antioxidative enzymes

Abstract: :  Melatonin, the main secretory product of the pineal gland, is known to collaborate against oxidative stress within cells, but its mechanism of action in terms of stimulating antioxidant enzymes remains unclear. Herein, we propose that melatonin modulates antioxidant enzyme activities via its interaction with calmodulin, which in turn inhibits downstream processes that lead to the inactivation of nuclear RORα melatonin receptor. Eventually, this nuclear transcription factor downregulates NF‐κB‐induced antiox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
332
2
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 450 publications
(350 citation statements)
references
References 69 publications
(89 reference statements)
11
332
2
5
Order By: Relevance
“…В настоящее время в литературе активно обсуждается регуляторная и стимулирующая роль мелатонина в отношении функционирования системы антиоксидантных ферментов в различных условиях [12,13]. Современные научные сведения о влиянии мелатонина на дисбаланс продукции активированных кислородных метаболитов и антиоксидантной защиты организма в различных патологических состояниях неоднозначны.…”
unclassified
“…В настоящее время в литературе активно обсуждается регуляторная и стимулирующая роль мелатонина в отношении функционирования системы антиоксидантных ферментов в различных условиях [12,13]. Современные научные сведения о влиянии мелатонина на дисбаланс продукции активированных кислородных метаболитов и антиоксидантной защиты организма в различных патологических состояниях неоднозначны.…”
unclassified
“…These effects of melatonin are related with scavenging of a variety of toxic oxygen and nitrogen-based reactants and stimulation of antioxidative enzymes. 17,18 It has been shown that postoperative elevated values of TNF-a, IL-6, and IL-8 reduced by melatonin in newborns. 19 Lipopolysaccharide (LPS)-induced TNF-alpha production reduced in human monocytes by melatonin.…”
Section: Introductionmentioning
confidence: 99%
“…This result is consistent with findings of previous studies that suggested the possibility of prevention of genotoxic effects resulting from chemotherapy, by using HF. 37,38 Several explanations have been offered for anti-mutagenic activity of honey, the mechanisms of the protective of honey against CP genotoxicity may be due to one or more of the following: antioxidant action 39,40 and to stimulate the antioxidative enzyme glutathione peroxidas, 41 leading to an increase in antioxidant capacity of the cells which might fortify the efficiency of protective pathways against cytogenetic damage in CP exposure, 42 therefore, it has been used as a compared group with other types of honey's used in this investigation. it is clear that there were high significant differences in frequencies of MN between the groups which treated with both honey formed by supplementary feeding (HS and/or HW) respectively, in three interactions used (before, after, with treatment) (Tables 3 and 4).…”
Section: Resultsmentioning
confidence: 99%